2013
DOI: 10.1039/c3sc50554e
|View full text |Cite
|
Sign up to set email alerts
|

A platinum anticancer theranostic agent with magnetic targeting potential derived from maghemite nanoparticles

Abstract: Superparamagnetic iron oxide nanoparticles (SPION) are potential drug carriers and a magnetic resonance imaging (MRI) contrast agent for cancer therapy and diagnosis. In this study, dechlorinated cisplatin (CMDP) is tethered to maghemite nanoparticles modified with 4-oxo-4-(3-(triethoxysilyl)propylamino)butanoic acid (OTPBA-SPION) through the surface carboxylate groups. The nanocomposite (CMDP-OTPBA-SPION) was characterized by TEM, XPS, EDX, SQUID, ICP-AES, and zeta potential. A relatively high Pt loading capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…For example, the immobilization of cisplatin onto carboxy‐functionalized superparamagnetic iron oxide nanoparticles (SPION) in the work of Wang et al . did not result in an improved cytotoxic effect when compared with free cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the immobilization of cisplatin onto carboxy‐functionalized superparamagnetic iron oxide nanoparticles (SPION) in the work of Wang et al . did not result in an improved cytotoxic effect when compared with free cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…The decay rate is not only dependent on iron oxide concentration, but also on temperature, particle size, and coating of the iron oxide cores. 8, 9, 75 To determine if the protein corona affected the T 2 relaxation time, we carried out the same measurement using isolated soft corona-SPIONs (Fig. 6B).…”
Section: Resultsmentioning
confidence: 99%
“…[8] We recently showed that Pt drugs could be attached to Fe 2 O 3 nanoparticles to form anticancer theranostic agents, in which nanoparticles act as both drug carriers and T 2 -weighted MRI contrast agents (CAs). [9] However, release procedures are indispensable for these nanomedicines. As alternatives, Gd III complexes are widely used as T 1 -weighted CAs in MRI through the interaction of innersphere water with paramagnetic Gd III and rapid exchange of the coordinated water with the bulk solvent.…”
Section: (Py)cl]mentioning
confidence: 99%